Determinants of Forensic Accounting Usage Intention Among Internal Auditors in Indonesian Mining Firms - Sylvia Fitriani; Gatot Soepriyanto (Ilomata International Journal of Tax and Accounting, 2026)
Financial fraud and structural corruption in the Indonesian coal mining sector remain pervasive issues that necessitate the implementation of advanced investigative techniques such as forensic accounting. Drawing on the Theory of Planned Behavior (TPB) and Stakeholder Theory, this study examines how four constructs, forensic accounting perception (as a proxy for attitude), stakeholder pressure (representing subjective norms), internal control effectiveness (reflecting perceived behavioral control), and fraud risk awareness (as a cognitive stimulus), shape internal auditors’ intention to adopt forensic accounting practices within this high-risk extractive context. A quantitative explanatory research design was implemented by surveying 41 internal auditors from companies holding Izin Usaha Pertambangan (IUP) with a minimum of three years of professional experience, and data analysis was executed through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4 software. Empirical results demonstrate that forensic perception (β = 0.205, p < 0.05), internal control effectiveness (β = 0.300, p < 0.05), and fraud risk awareness (β = 0.340, p < 0.05) significantly and positively influence adoption intention, with the model explaining 86.1% of the variance (R² = 0.861). Stakeholder pressure yields a significant negative effect (β = −0.618, p < 0.05), which may suggest that auditors perceive coercive external demands as a threat to professional autonomy rather than a value-adding requirement, consistent with institutional reactance mechanisms. These findings indicate that internal drivers such as robust governance structures and proactive risk awareness may serve as the primary catalysts for fostering forensic accounting adoption intention. Regulators may consider complementing mandates with supportive capacity-building frameworks to reduce potential resistance, noting that this study examines intention rather than observed adoption behavior. However, this study is subject to cross-sectional, self-reported, and intention-based limitations that warrant cautious interpretation and further longitudinal investigation.